Features distinguishing clinically amyopathic juvenile dermatomyositis from juvenile dermatomyositis. (16th July 2018) - Mamyrova, Gulnara; Kishi, Takayuki; Targoff, Ira N; Ehrlich, Alison; Curiel, Rodolfo V; Rider, Lisa G; ,
Abstract: Objective: We examined features of clinically amyopathic JDM (CAJDM), in which patients have characteristic rashes with little to no evidence of muscle involvement, to determine whether this is a distinct phenotype from JDM. Methods: Demographic, clinical, laboratory and treatment data from 12 (9 hypomyopathic, 3 amyopathic) patients meeting modified Sontheimer criteria for CAJDM and from 60 matched JDM patients meeting Bohan and Peter criteria were examined. Differences were evaluated by Fisher's exact and Mann–Whitney tests, random forests and logistic regression analysis. Results: Nine (75%) CAJDM patients had anti-p155/140 (transcriptional intermediary factor 1), one (8.3%) anti-melanoma differentiation-associated gene 5 autoantibodies and two (16.7%) were myositis autoantibody negative. CAJDM patients were younger at diagnosis and frequently had mild disease at onset. CAJDM patients had less frequent myalgias, arthritis, contractures, calcinosis, dysphagia, abdominal pain and fatigue. The muscle, skeletal and overall clinical scores were lower in CAJDM. Serum muscle enzymes were less frequently increased in CAJDM, and peak values were lower. CAJDM patients received fewer medications compared with JDM patients. Only 50% of CAJDM patients received oral prednisone, but the maximum dose and treatment duration did not differ from JDM. At a median follow-up of 2.9 years, CAJDM patients had no documented functional disability, and none developed weakness, calcinosis, interstitial lung disease or lipodystrophy. Multivariable modelling revealed a lower skeletal score and less frequent myalgias as the most important factors in distinguishing CAJDM from JDM. Conclusion: CAJDM may be distinguished from JDM, in that they often have p155/140 (transcriptional intermediary factor 1) autoantibodies, have fewer systemic manifestations and receive less therapy.